1993
DOI: 10.1108/08858629310044183
|View full text |Cite
|
Sign up to set email alerts
|

Sales Teamwork: A DOMINANT STRATEGY FOR IMPROVING SALESFORCE EFFECTIVENESS

Abstract: Reports the findings of a national study which addresses the question: why do some salesforces perform much better than others? Features an in‐depth presentation of the results pertaining to the teamwork factor and recommends managerial actions to take. Relates the key findings, examines the measures used to determine salesforce performance, and identifies teamwork variables constituting the dominant strategies which result in increasing salesforce effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…The result in this study provides empirical evidence that of highly significant impact of teamwork on KPI achievement (β = 0.251, t-Value = 2.695). This result is consistent with El-Ansary et al (1993) and Rabey (2003) who found the performance could be enhanced by the synergy of teamwork. The possible reason could be regular interactions between the employees and superior will encourage, intensify the bonds, and create an auspicious of organizational environment.…”
Section: Teamworksupporting
confidence: 91%
“…The result in this study provides empirical evidence that of highly significant impact of teamwork on KPI achievement (β = 0.251, t-Value = 2.695). This result is consistent with El-Ansary et al (1993) and Rabey (2003) who found the performance could be enhanced by the synergy of teamwork. The possible reason could be regular interactions between the employees and superior will encourage, intensify the bonds, and create an auspicious of organizational environment.…”
Section: Teamworksupporting
confidence: 91%
“…Barker (1997) claims that``automated salespeople'' are on average three times more productive than sales staff in firms without IT-related selling facilities because computer technology contributes substantially to sales forecasting and planning, the rapid provision of customer contact and status information, and the accumulation of knowledge about markets, distribution channels, customer service requirements, etc. Note moreover how teamwork and knowledge sharing is known to be critically important for improving sales force effectiveness (El-Ansary et al, 1993;Barker, 1997).…”
Section: The Investigationmentioning
confidence: 99%
“…The specific role of sales management in assisting salespeople to perform well is less clear. One industry-based study identified five factors which contribute to a high performance salesforce (El-Ansary et al, 1993). These influences are sales teamwork, sales training, supplier relations, hiring practices, and sales manager characteristics.…”
Section: Introductionmentioning
confidence: 99%